The construction of Latina/o literary imaginaries : essays on alternative worldviews - Kabalen de Bichara, Donna M. (Cambridge Scholars Publishing, 2018)
This book explores the cultural and historical imaginary expressed in literary works that emphasize Latina/o world views. The essays here employ critical approaches based on discourse and cultural analyses that highlight individual and collective identity. They encompass a wide spectrum of topics that deal with border newspapers published early in the twentieth century and their function as a forum for conserving memory based on cultural values and religious beliefs; life writing and fictional rewritings of memory; autobiographical texts that emphasize the diasporic experience of immigrants; a.
Keywords: American literature -- Hispanic American authors -- History and criticism.; Hispanic Americans in literature.; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique.; Américains d'origine latino-américaine dans la littérature.; LITERARY CRITICISM -- American -- General.; American literature -- Hispanic American authors; Hispanic Americans in literature; Criticism, interpretation, etc.